Marketing estratégico para el posicionamiento de la marca Centro de Desarrollo Infantil Tía Uchy en la ciudad de Guayaquil - Ramírez Andrade, Tabata Lissette (2023)
The present study was directed at the design of marketing strategies for the positioning of the brand "Tia Uchy Children's Development Center" where it carries out its activities in the city of Guayaquil. The children's center has a varied and complete educational system so that parents are sure that the service provided is the best and that this should be made known to more people for their professional growth, this is linked to their constant learning that the medium develops in updating its knowledge, despite having a quality service the brand has not been able to position itself as one of the best for this the research project is based on theories that will help establish the strategies that must be taken together to a field investigation of the personnel in knowing the current situation regarding the problem raised and to the parents who are willing to pay for the service, the collection of the acquired data has helped in the effective interpretation of the development of a feasible proposal for the Tía Uchy Child Development Center. This has helped to create strategies focused on the brand and its positioning, such as the creation of a website for the search for information and its audiovisual content for the positioning and recognition of the brand, as well as the creation of activities that give know the institution.